SISTEM KONTROL DAN MONITORING PEMBANGKIT LISTRIK TENAGA ANGIN UNTUK PENERANGAN BAGAN BERBASIS IOT - Rendy Afreza; Annisa Ummihani; Eko Sulistyo; Indra Dwisaputra (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Explanation of the chart currently still uses generators as an energy source to turn on the lights at night, so it requires relatively high operational costs to buy fuel oil, besides the use of fuel oil has a negative impact on the environment because it can cause environmental damage. Therefore, alternative energy sources are needed to overcome these problems. In this study, it is proposed to make a PLTB with a power of 300 Watt with an IoT system placed in the chart aiming to reduce the operational costs incurred by fishermen to buy generator fuel by utilizing the wind available in nature. The methodology for making this PLTB uses a 300 Watt DC generator with a 3 blade HAWT wind turbine which is controlled using an INA219 sensor, a BH1750, and an anemometer sensor with a monitoring system utilizing IoT-based technology using a website. The test will be carried out by testing the effect of wind speed on the generator output voltage and current, battery charging time, battery usage time on lamp load, and monitoring system using the website. Based on the test results obtained data with a minimum wind speed of 2 m/s the power generated by the generator is 0.378 Watt and the maximum power is achieved when the wind speed is 9 m/s. In this PLTB it takes 12 hours to charge the battery with a capacity of 7.2 AH to full with a charging current of 0.66 A, while for discharging the battery using a 10 Watt DC lamp load it takes 6 hours. The monitoring system at the generator using the website functions properly so that the data obtained from the generator can be monitored in real time and stored in the database.